Building inclusive preschool classrooms: How desirable and feasible is a set of strategies that facilitate teacher-child relationships? - Sanches-Ferreira, Manuela; Gonçalves, Joana L.; Araújo, Sara Barros; Alves, Sílvia; Barros, Sílvia (Frontiers in Education, 2022)
Positive teacher-child relationships promote children’s engagement, as children feel more secure to explore and participate in free or oriented activities. For children with disabilities, a context wherein they can receive the support to maintain a positive engagement in different activities is even more relevant. A scarcity of research exists on how to promote ECEC quality, namely, how to facilitate teacher-child interactions in inclusive environments. This study aims to evaluate preschool teachers’ opinions about the desirability and feasibility of a set of empirically validated strategies to improve teacher-child interactions in ECEC classrooms, for the group and children with disabilities. The participants were 89 Portuguese preschool teachers. Based on a non-systematic literature review, a questionnaire composed of 22 strategies to facilitate teacher-child interactions (in 4 dimensions: emotionally responsive interactions, classroom management, attend to children`s perspectives, and scaffolding learning) was developed. Along with the questionnaire, a set of socio-demographic variables was also collected. ECEC teachers scored significantly higher in the desirability subscale compared with the feasibility subscale in all dimensions and at both the child and the group level. This gap between teachers’ perceived desirability and feasibility provides important insights regarding the dimensions which are important to reinforce in ECEC teachers’ education and professional development. The mean difference between the desirability and feasibility subscales registered a higher effect size at the child’s level than at the group’s level, confirming that the inclusion of children with disabilities in preschool settings remains a challenge. Moreover, the effect size was small to moderate in the Emotionally Responsive Interactions dimension for both child and group levels. These results are aligned with previous studies stating that among different self-identified dimensions for improvement, emotional support is the less evoked by ECEC teachers. Across all dimensions, the main reason teachers give for difficulty in feasibility, both at the group and child’s level, is lack of knowledge. Overall, understanding the reasons teachers attribute to the difference between the strategies’ desirability and feasibility informs the assessment of teacher education needs and might be operationalized as a new observation instrument.